Innovación aplicada al desarrollo del liderazgo lasaliano en Brasil: fundamentos para la excelencia en la gestión (2020)
This article addresses the application of the fundamentals of management excellence to leadership development at La Salle University (Unilasalle), Brazil. Leading is an exercise that requires self-knowledge and constant improvement of skills and competencies. When it comes to innovation applied to leadership, good practices and new management support methodologies are essential to help the practice of leadership. Based on this, the objective of this article is to present the process of organizational leadership development at Unilasalle. The methodology is based on documentary analysis, field diary and statements of leaderships and the perception of the teams. Results indicate: systematized and continuous training of leaders; strategic choice of participants; management by competencies; personalized self-development and adjustment of the leadership development practice of Unilasalle based on its principles and values. It concludes with the need to train people with technical, human and cross-cutting capabilities, with a focus on innovative, strategic and results-based management. The attitudes of transformational leadership necessarily go through a detailed work plan and organization, which are fundamental to the success of the exercise of leadership.